2015
DOI: 10.1039/c5nr02753e
|View full text |Cite
|
Sign up to set email alerts
|

Chelator free gallium-68 radiolabelling of silica coated iron oxide nanorods via surface interactions

Abstract: The commercial availability of combined magnetic resonance imaging (MRI)/positron emission tomography (PET) scanners for clinical use has increased demand for easily prepared agents which offer signal or contrast in both modalities. Herein we describe a new class of silica coated iron-oxide nanorods (NRs) coated with polyethylene glycol (PEG) and/or a tetraazamacrocyclic chelator (DO3A). Studies of the coated NRs validate their composition and confirm their properties as in vivo T2 MRI contrast agents. Radiola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 52 publications
(99 reference statements)
2
38
0
1
Order By: Relevance
“…In general, small molecule-based 68 Ga imaging agents lack the cell-membrane permeability if no carrier or cell-targeting agent is attached to the molecules. 27 This has hampered the progress made in the past two decades in the development of 68 Ga-based PET radiopharmaceuticals for cellular imaging applications. The surface functionalization of a fluorescent dye on these NPs was explored to visualize cellular uptake of Ga@PBNPs in HeLa cells by confocal fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…In general, small molecule-based 68 Ga imaging agents lack the cell-membrane permeability if no carrier or cell-targeting agent is attached to the molecules. 27 This has hampered the progress made in the past two decades in the development of 68 Ga-based PET radiopharmaceuticals for cellular imaging applications. The surface functionalization of a fluorescent dye on these NPs was explored to visualize cellular uptake of Ga@PBNPs in HeLa cells by confocal fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…[32] Their inability to absorb wavelengths in the electromagnetic spectrum and non-interference with the magnetic fields has been utilized in complexing with other functional nanomaterials and drugs to design multifunctional agents (Table 2). [3335] Moreover, high surface area-to-volume ratio, rigid and stable skeletal network and well-established, scalable synthetic procedures are added advantages, propelling their application as contrast agents in cancer theranostics.…”
Section: Radiolabeled Nanomaterials For Cancer Theranosticsmentioning
confidence: 99%
“…Taking advantage of the easily tailorable chemistry of silica, Burke et al synthesized 68 Ga radiolabeled silica coated iron oxide nanorods to combine the high sensitivity of PET with MR contrast. [35] As with 89 Zr, 68 Ga is a hard Lewis acid that coordinates easily and stably with the Lewis base donor atoms like oxygen from the silanol groups. PEG modified nanoconjugates were further used for high sensitivity liver imaging.…”
Section: Radiolabeled Nanomaterials For Cancer Theranosticsmentioning
confidence: 99%
“…This method is also effective for radiolabeling silica-coated IONP with 68 Ga, showing the versatility of the method. 39 An analogous method for radiolabeling the clinically approved IONP Feraheme, coined heat-induced radiolabeling (HIR) by the authors, was demonstrated and may be a route for radiolabeling other metal oxide NPs with oxophilic tracers. 38 Omitting the IONP core, chelator free loading of 89 Zr was also observed using various molecular weight dextran NPs for PET/CT imaging of lymph node drainage as well as Cerenkov-guided tumor resection.…”
Section: Pet Imagingmentioning
confidence: 99%